Expression of Estrogen Receptors β and ß1 in Tissue of Human Non-Small Cell Lung Cancer - A. S. Shaturova; T. A. Bogush; E. A. Dudko; G. YU. Chemeris; R. YU. Ramanauskaite; I. D. Kalganov (Антибиотики и Химиотерапия)
Comparability of the level and intensity of estrogen receptors ß (ERß expression in non-small cell lung cancer tissue of 32 patients was analyzed by flow cytometry using various antibodies - to the total fraction of ERß (clone 14C8) as well to the full-length ERß1 isoform (clone EMRO2). The differences in the ER expression indexes detected by anti-ERß or anti-ERß1 antibodies were revealed in some patients, but it had no influence on average indexes of the ERß expression in the patient groups investigated. It was confirmed by the findings on more frequent and more intensive expression of ERß in the non-small cell lung cancer tissue of female patients vs. the males irrespective of antibody type - anti-ERß or anti-ERß1. Therefore, in comparative analysis of ERß expression in the groups of the patients with different clinicomorphologic characteristics of the disease it is possible to use both the antibodies. For individual disease prognosis in the routine clinical practice it is recommended to use the antibodies to the total fraction of ERß, since there are individual differences between the ERß expression indexes revealing by various types of antibodies.